Seroprevalence of anti-Toxoplasma gondii antibodies in wild boars (Sus scrofa), hunting dogs, and hunters of Brazil - Machado, Fernanda Pistori; Kmetiuk, Louise Bach; Teider-Junior, Pedro Irineu; Pellizzaro, Maysa; Yamakawa, Ana Carolina [UNESP]; Martins, Camila Marinelli; Van Wilpe Bach, Renato; Morikawa, Vívien Midori; De Barros-Filho, Ivan Roque; Langoni, Hélio [UNESP]; Dos Santos, Andrea Pires; Biondo, Alexander Welker (Public Library of Science (PLoS), 2019)
Seroprevalence of Toxoplasma gondii has been extensively studied in wild boars worldwide due to the emerging risk for human infection through meat consumption. However, this is the first study that reports toxoplasmosis seroprevalence in wild boars, wild boar hunters and their hunting dogs. The aim of the present study was to evaluate the seroprevalence of anti-T. gondii antibodies in the complex wild boars, hunting dogs and hunters, and to determine the risk factors associated with seropositivity in southern and central-western Brazil. Overall, anti-T. gondii seropositivity was observed in 15/71 (21.1%) wild boars by modified agglutination test (MAT); and 49/157 (31.2%) hunting dogs and 15/49 (32.7%) hunters by indirect immunofluorescent antibody test (IFAT). Seroprevalence of toxoplasmosis in Brazilian wild boars was within the national and international range, posting wild boars as potential environmental sentinels for T. gondii presence. In addition, the findings have comparatively shown that wild boars have been less exposed to infection than hunting dogs or hunters in both Brazilian regions. Seropositivity for T. gondii was statistically higher in 12/14 (85.7%) captured wild boars when compared to 5/57 (7.0%) free-range wild boars (p = 0.000001). Similarly, captured wild boars from anthropized areas were more likely to be seropositive than of natural regions (p = 0.000255). When in multiple regression model, dogs with the habit of wild boar hunting had significant more chance to be positive (adjusted-OR 4.62 CI 95% 1.16-18.42). Despite potential as sentinels of environmental toxoplasmosis, seroprevalence in wild boars alone may provide a biased basis for public health concerns; thus, hunters and hunting dogs should be always be included in such studies. Although hunters should be aware of potential T. gondii infection, wild boars from natural and agricultural areas may present lower protozoa load when compared to wild boars from anthropized areas, likely by the higher presence of domestic cats as definitive hosts.